Growth Response of Carrot (Daucus Carota) Local and Hybrids Varieties on Different Pb Doses - Boy Indra Permata; Nasrez Akhir; Zulfadly Syarif (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2017)
This research aimed to analyse the growth and yield of local and hybrid carrots (Daucus carota) on various heavy metal (Pb) doses. The experiments had been done in Nagari Situjuah Limo Nagari, Kabupaten Lima Puluh Kota from August to December 2015. The purpose of this experiment was to obtain the safe doses of Pb for growth and yield of carrots as food consumption. Treatments were arranged in a split plot design with three replications. The treatments were four doses of Pb (0, 100, 200 and 300 mg/10 kg soil) and varieties (local and hybrid carrots). Data were analysed by variance analysis α=1%, and Duncan's Multiple Range Test (DMRT) with α=1%. The results showed that various doses of heavy metal Pb affected significantly different of Pb content in leaves, yields, and chlorophyll. Local and hybrid carrots had significantly difference in plant height, long leaves, yields weight and diameter, Pb doses in leaves and yields and chlorophyll. Pb contamination levels in leaves and the leaves exceeded the limits set by Indonesian National Standard (SNI)